2006
DOI: 10.1002/ajh.20524
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferation effects of oridonin on HPB-ALL cells and its mechanisms of action

Abstract: Oridonin, an ent-kaurane diterpenoid derived from the herbal Rabdosia rubescens, has been recently reported to have antitumor effects on a large variety of cancer cells. The present study was undertaken to investigate the in vitro antiproliferation and apoptosis inducing effects of oridonin on HPB-ALL cell lines and its mechanisms of action. HPB-ALL cells in culture medium in vitro were treated with different concentrations of oridonin (16-56 mmol/L). MTT assay was used to detect the cell growth inhibitory rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The anticancer activity of oridonin is thought to rely on its ability to inhibit cell growth, reduce angiogenesis, and enhance apoptosis (Chen et al 2005; Ikezoe et al 2003; Liu et al 2004, 2006; Meade-Tollin et al 2004; Zhang et al 2004a). Oridonin inhibits cell growth and induces apoptotic cell death in many cancer cell lines, including leukemia (NB4, HL-60, HPB-ALL, Kasumi-1), glioblastoma (U118, U138), melanoma (A375-S2), cervical carcinoma (HeLa), ovarian carcinoma (A2780, PTX10), prostate carcinoma (LNCap, Du145, PC3), breast carcinoma (MCF-7, MDA-MB231), murine fibrosarcoma (L929), and non–small-cell lung carcinoma (NCI-H520, NCI-H460, NCI-H1299) (Chen et al 2005; Ikezoe et al 2003; Liu et al 2004, 2006; Zhang et al 2004a). The reported doses needed for growth inhibition and apoptosis vary significantly among different groups using different cell lines, ranging from 0.5 μM (0.18 μg/mL) in Kasumi-1 cells to 56 μM (20.4 μg/mL) in HPB-ALL cells (Liu et al 2006; Zhou et al 2007b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer activity of oridonin is thought to rely on its ability to inhibit cell growth, reduce angiogenesis, and enhance apoptosis (Chen et al 2005; Ikezoe et al 2003; Liu et al 2004, 2006; Meade-Tollin et al 2004; Zhang et al 2004a). Oridonin inhibits cell growth and induces apoptotic cell death in many cancer cell lines, including leukemia (NB4, HL-60, HPB-ALL, Kasumi-1), glioblastoma (U118, U138), melanoma (A375-S2), cervical carcinoma (HeLa), ovarian carcinoma (A2780, PTX10), prostate carcinoma (LNCap, Du145, PC3), breast carcinoma (MCF-7, MDA-MB231), murine fibrosarcoma (L929), and non–small-cell lung carcinoma (NCI-H520, NCI-H460, NCI-H1299) (Chen et al 2005; Ikezoe et al 2003; Liu et al 2004, 2006; Zhang et al 2004a). The reported doses needed for growth inhibition and apoptosis vary significantly among different groups using different cell lines, ranging from 0.5 μM (0.18 μg/mL) in Kasumi-1 cells to 56 μM (20.4 μg/mL) in HPB-ALL cells (Liu et al 2006; Zhou et al 2007b).…”
mentioning
confidence: 99%
“…Oridonin induced p21 expression, resulting in cell cycle arrest in LNCaP and NCI-H520 cells (Ikezoe et al 2003). Oridonin activated the caspase 3–dependent apoptotic pathway through up-regulation of Bax and down-regulation of Bcl-2, which promotes release of cytochrome c (Chen et al 2005; Liu et al 2006). Inhibition of telomerase activity has been reported to be another mechanism that contributes to the anticancer function of oridonin (Liu et al 2004).…”
mentioning
confidence: 99%
“…By flow cytometric analysis, the polyphenol fraction was demonstrated to induce G 0 /G 1 cell growth arrest and cell apoptosis in DU-145 and PC-3 triggered by caspase-3 activation (34,35). Since oridonin (36,37), baicalein, wogonin (38)(39)(40) and ISL (41) are known to stimulate caspase-3 activation, the apoptosis of LNCaP and DU-145 observed in Fig. 1 was likely caused by the same mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Since then, studies have focused mainly on the anti-tumor effect of oridonin and its mode of action. Based on the studies of the anti-tumor pharmacodynamics of oridonin, in vitro tests have shown that oridonin has an inhibitory effect on such human cancer cell lines as: leukemias (HL60 [6,7] , K562 [8,9] , HPB-ALL [10] , NB4 [11] , Jurkat [12] ); esophageal cancers (CaEs-17 [13] ); gastric cancer (MGC80-3 [13] ); liver cancer (BEL-7402 [ 13,14] ); nasopharyngeal cancer (CNE [13,15] ); lung cancers (SPCA1 [16] , NCI-H520 [11] , N C I -H 4 6 0 [ 11 ] , N C I -H 1 2 9 9 [ 11 ] ) ; b r e a s t c a n c e r s ( M C F 7 [ 11 , 1 7 , 1 8 ] , MDA-MB231 [11] ); ovarian cancers (A2780 [18] , PTX10 [18] ); uterine cervix cancer (Hela [13,17,19] ) and prostatic cancers (LNCaP [11] , DU145 [11] , PC3 [11] ). Oridonin is a water-insoluble diterpene compound which is not easily absorbed when taken orally, and there is no preparation for intravenous infusion.…”
Section: Discussionmentioning
confidence: 99%